2016
DOI: 10.18632/oncotarget.8821
|View full text |Cite
|
Sign up to set email alerts
|

USP14 is a predictor of recurrence in endometrial cancer and a molecular target for endometrial cancer treatment

Abstract: Endometrial adenocarcinoma is the most common gynecologic malignancy in the United States. Most endometrial cancer cases are diagnosed at an early stage and have good prognosis. Unfortunately a subset of patients with early stage and low grade disease experience recurrence for reasons that remain unclear. Recurrence is often accompanied by chemoresistance and high mortality.Deubiquitinating enzymes (DUBs) are key components of the ubiquitin-dependent protein degradation pathway and act as master regulators in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…These results suggest that activated Akt in Pten-negative cancer cells might be able to stabilize a significant portion of the proteome by inhibiting both UPS and autophagy through regulating USP14 to promote tumorigenesis. Consistent with this possibility, increased expression of USP14 has been found in a variety of cancers, including multiple myeloma (Tian et al 2014), colorectal cancer (Shinji et al 2006), lung cancer (Wu et al 2013), epithelial ovarian cancer (Wang et al 2015), and endometrial cancer (Vogel et al 2016). Future studies will be needed to elucidate the functional role of elevated USP14 expression in tumorigenesis.…”
Section: Discussionmentioning
confidence: 78%
“…These results suggest that activated Akt in Pten-negative cancer cells might be able to stabilize a significant portion of the proteome by inhibiting both UPS and autophagy through regulating USP14 to promote tumorigenesis. Consistent with this possibility, increased expression of USP14 has been found in a variety of cancers, including multiple myeloma (Tian et al 2014), colorectal cancer (Shinji et al 2006), lung cancer (Wu et al 2013), epithelial ovarian cancer (Wang et al 2015), and endometrial cancer (Vogel et al 2016). Future studies will be needed to elucidate the functional role of elevated USP14 expression in tumorigenesis.…”
Section: Discussionmentioning
confidence: 78%
“…35,36 The USP 14, one of the USP family enzymes, was shown to predict the endometrial cancer recurrence. 37 Although it was limited to the stage I endometrial cancer, it was a pioneer study suggesting the potential of drugs targeted against deubiquitinating enzymes in endometrial cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown that the UPS pathway plays an indispensable role in the regulation of mitochondrial energy metabolism by regulating the turnover of several mitochondrial oxidative phosphorylation (OXPHOS) proteins such as the succinate dehydrogenase subunit A (SDHA), the mitochondrial respiratory complex II [63,64]. Findings also indicate a mechanism of crosstalk between the proteasome and autophagy pathway [65][66][67][68][69]. This includes the degradation of synaptosomal-associated protein 29 (SNAP29) and syntaxin 17 (STX17) by the ubiquitin-independent 20S proteasome [70].…”
Section: The Ups and Tumor Metabolismmentioning
confidence: 99%